Audiences’ Perception of Rape Euphemism In the Sexual Violence News in Online Media - Ade Devia Pradipta; Putu Titah Kawitri Resen (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2024)
Online media is a form of mass media that is close to society, especially in the era of increasingly massive development of information and communication technology. One type of information that the public is interested in in online media is news, especially cases of sexual violence such as rape. Rape is a serious crime because it harms the victim from physical and psychological aspects. Reporting about rape incidents generally applies euphemisms for verbs that represent heinous acts. In some cases of rape, the criminal act is replaced with several words such as